RANCANG BANGUN TACHOMETER DIGITAL BERBASIS ARDUINO DILENGKAPI CHARGING DAN MODE PENYIMPAN DATA - Harsoyo, Imam Tri; Nugroho, Andi Kurniawan; Nuriman, Nuriman (Elektrika, 2019)
A good and feasible centrifuge is needed in the world of health, therefore a digital tachometer is needed to calibrate a centrifuge. Digital tachometer is a measuring instrument used to measure the rotation speed of a motor. This tachometer will be tested to function by being compared to using Digital Laser Photo Tachometer. This tachometer will display the number of rotations per minute of a motor according to the speed setting on the centrifuge using the output of this E18-D80NK sensor which will later be processed by the Arduino Nano. As for this feature charger and data storage mode, so that user can save the data of measurement results on SD Card, and beside that user can also be a way of charging when after usage or before usage. At testing the tool used point settings 1000, 2000, 3000, 4000, 5000, and 12000 RPM. Based on the measurement results of centrifuge using tachometer module and comparison tachometer have average percentage of error varying at each setting point. The smallest error 0.8% at the setting Point 3000 RPM, while the largest error 4.9% at the setting point 1000 RPM. The Tacometer error value on this Centrifuge measurement is still within the tolerance limit of ± 10%